ІНТЕРПРЕТАЦІЯ ХУДОЖНЬОГО ОБРАЗУ: АСПЕКТИ ПОЕТИКИ І МЕТОДИКИ - Тичініна, Альона Романівна; Наместюк, Світлана Валеріївна (Вісник науки та освіти, Видавнича група «Наукові перспективи», 2023)
ARTISTIC IMAGE INTERPRETATION: ASPECTS OF POETICS AND METHODS Abstract. The article under discussion outlines the specifics of studying the artistic image in terms of topical issues of contemporary poetics, as well as in relation to teaching certain literary disciplines. The problem has been examined on the example of the courses required for the educational training of teachers of philological disciplines, in particular, Ukrainian literature and world literature: “History of World Literature”, “Introduction to Literary Studies”, “Literary Theory”, “Methods of Teaching World Literature”, and “Analysis of a Literary Text in Literature Classes”. The research highlights the peculiarities of the emergence and functioning of the artistic image in various forms of art (music, painting, architecture, literature). The article also emphasizes the peculiarities of poetic art as thinking in verbal images. The purpose of the article is to thoroughly consider the artistic image as a category of artistry, to comment on the most important doctrines of the artistic image in terms of poetics and teaching methods, to present a typology of artistic images in a literary text, and to highlight their functions. The methodology of the study is theoretical poetics, historical poetics, intermediality, and receptive poetics. The outcomes of the study emphasize the terminological differences between the concepts of character, hero, protagonist, actor, system of images, personosphere, narrator, as well as the importance of their differentiation within the courses of university educational programs. A detailed investigation of the reception of the artistic image of the apple in representative examples of poetry and prose in foreign and Ukrainian literature (ancient Greek mythology, the Bible, texts by J. Milton, F. Kafka, R. M. Rilke, R. Kunze, M. Rylsky, A. Malyshko), painting (works by L. Cranach the Elder, Titian, K. Bilokur, R. Magritte, M. Taylor) and cinema (“Adam’s Apples”) made it possible to draw conclusions about the potential functioning of a certain artistic image in various forms – autology, metaphor, allegory, symbol, traditional image, phraseological unit. The article also identifies the specifics of the artistic image, which is the fundamental basis of literature as an art of words, the basic category of poetics, and an urgent issue in the field of teaching methods. This thematic component not only forms the fundamental knowledge, skills and abilities of a philologist-scientist and a philologistteacher, but also develops students’ creative thinking within the respective educational programs.
Keywords: українська література; зарубіжна література; художній образ; поетика; жанр; персоносфера; наратив; інтермедіальність; символ